A method for the staining of intraosseous nerve fibers using Sihler's staining technique. (August 2013) - Shiozaki, K; Miida, K; Tanaka, R; Shimoda, S
Abstract Understanding nerve fiber distribution in the jaw bone is important when performing invasive surgical treatments. Both microscopic and macroscopic anatomical techniques have been developed to study innervation. Conventional methods of removing and staining these structures, however, often alter structure and lack reproducibility of the resulting specimens. We sought to optimize Sihler's staining technique to stain intraosseous nerves in mandibles. Four cadaver specimens were used. The best staining of intraosseous nerve fibers was achieved by using the Plank-Rychlo solution. When the Styrene monomer was used, the resulting transparency was better than that obtained with glycerin under the same conditions. No significant differences were found between Sihler's staining procedure performed according to the conventional method and the procedure in which the second decalcification step was omitted. Our results demonstrate that applying Sihler's staining technique to bones makes them transparent and allows observation of nerves while preserving the external shape of the bone and maintaining the position of intraosseous nerve fibers. Our findings suggest our Sihler staining method for intraosseous nerve fibers can provide an intermediate resolution between macroscopic and microscopic techniques.